1994
DOI: 10.1002/ana.410350606
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of human auditory cortex

Abstract: Magnetic resonance imaging methods recently demonstrated regional cerebral signal changes in response to limb movement and visual stimulation, attributed to blood flow enhancement. We studied 5 normal subjects scanned while listening to auditory stimuli including nonspeech noise, meaningless speech sounds, single words, and narrative text. Imaged regions included the lateral aspects of both hemispheres. Signal changes in the superior temporal gyrus and superior temporal sulcus were observed bilaterally in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
154
2
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(181 citation statements)
references
References 57 publications
23
154
2
2
Order By: Relevance
“…The posterior region of the STG (along with the planum temporale, which was in the present study also activated by the modulations) including the upper bank of the STS have been reported to be involved in phoneme identification (Pöppel, 1996). In particular, regions along the banks of the STS have been shown to be involved in prelexical processing (Mummery et al, 1999) and perception of acoustic-phonological features of speech (Binder et al, 1994;Pöppel, 1996). One might draw a parallel between the interval structure of a chord and the phonological structure of a word.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The posterior region of the STG (along with the planum temporale, which was in the present study also activated by the modulations) including the upper bank of the STS have been reported to be involved in phoneme identification (Pöppel, 1996). In particular, regions along the banks of the STS have been shown to be involved in prelexical processing (Mummery et al, 1999) and perception of acoustic-phonological features of speech (Binder et al, 1994;Pöppel, 1996). One might draw a parallel between the interval structure of a chord and the phonological structure of a word.…”
Section: Discussionsupporting
confidence: 66%
“…It is important to note that the structures activated in the present experiment are also well known to be involved in the processing of language, as revealed by studies with both auditory (Zatorre et al, 1992;Mummery et al, 1999;Meyer et al, 2000b;Pöppel, 1996;Friederici et al, 2000a;Binder et al, 1994;Schlosser et al, 1998;Bellin et al, 2000;Friederici, 1998) and visual stimuli (Just et al, 1996;Shaywitz et al, 1995;Mazoyer et al, 1993). Especially the areas of Broca and Wernicke have been shown in numerous lesion-and imaging-studies to be critically involved in the processing of language.…”
Section: Discussionsupporting
confidence: 56%
“…When comparing the lexical to the null conditions (masked to exclude perceptual activation), the rhyming task produced activation in left superior and middle temporal gyri (BA 22,21) and left inferior frontal gyrus (BA 45,46), supporting the roles of these brain regions in phonological processing (Binder, et al 1994;Poldrack, et al 1999). Lexical activation included both dorsal (BA 45; pars opercularis) and ventral (BA 46; pars triangularis) aspects of the inferior frontal cortex.…”
Section: Lexical and Conflict Effectsmentioning
confidence: 81%
“…Right superior temporal gyrus activation has been linked to perception of pitch variation in linguistic and nonlinguistic stimuli (Johnsrude, et al 2000;Scott, et al 2000). Left superior temporal gyrus, on the other hand, has been implicated in access to phonological representations (Binder, et al 1994;Scott, et al 2000), and greater activation in left superior temporal gyrus was found to be correlated with higher accuracy and faster reaction times for auditory rhyme decisions in adults (Booth, et al 2003a). Activation in left inferior frontal gyrus may reflect reliance on phonological segmentation processes (Hagoort, et al 1999), increasing activation of motor programs involved in planning articulations (Rizzolatti and Craighero 2004) and/or greater top-down modulation of posterior regions associated with phonological processing (Bitan, et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In auditory language processing distinct peri-sylvian areas serve phonological properties [Binder et al, 1994;Jäncke et al, 1998;Wise et al, 1991], enable access to the meaning of words [Démonet et al, 1992;Fiez et al, 1996], or process the structural relations between words [Caplan et al, 1998;Dapretto and Bookheimer, 1999;Friederici et al, 2000a;Mazoyer et al, 1993]. Thus, a broadly distributed network involving the entire peri-sylvian cortex in the left hemisphere plays a predominant role in word-level, linguistic processing [Binder et al, 1996;Démonet et al, 1994].…”
Section: Introductionmentioning
confidence: 99%